Distribution of black carbon in sediments from mangrove wetlands in China - Wang, Min; Sun, Yuxin; Zeng, Huixian; Wu, Wenkun; Deng, Lifang; Tu, Panfeng (Frontiers in Forests and Global Change, 2022)
Black carbon (BC) is a carbonaceous residue generated by the incomplete combustion of fossil fuels and biomass. It forms an important component of the mangrove carbon pool. Although coastal and marine sediments have long been recognized as important sinks for BC, there are few reports on its distribution in mangrove sediments. This study investigated BC distribution and the associated environmental implications in sediments of various size fractions. Mangrove sediments were collected from 44 sites in the Guangdong, Guangxi, Hainan, and Fujian Provinces of China. Sediments from the Hainan Province were found to have much higher organic carbon (OC) and BC content than those from other provinces. Sediment OC and the BC content showed a significant positive relationship. Sediments from the Guangdong, Guangxi, and Hainan provinces showed significant BC accumulation with an enrichment factor > 1, especially in the size fractions 0.053–0.25 mm and 0.25–2 mm. Sediments from different sampling sites did not show significantly different BC distribution between the various size fractions. A higher mass loading of BC was observed among fine particles in samples from the Fujian Province, and among the larger particles in samples from the Guangdong, Guangxi, and Hainan provinces. Among all the samples, the BC/OC ratio ranged from 0.21 to 0.29, indicating that BC originates from a combination of biomass and mineral combustion. The average δ13C values in the sediments varied between the sampling plots. The highest δ13C values were recorded in the Fujian province, which indicates the proportion of BC from biomass combustion in mangroves in Fujian Province is higher than that in other Provinces.